Efficacy of Eupatorium Adenophorum Extract against Pulse Beetle (Callosobruchus chinensis) at Paklihawa Campus, Rupandehi - Mishra , Rajendra; Khanal , Subodh; Khanal , Dipak; Mishra , Saroj Raj (Journal of the Institute of Agriculture and Animal Science, 2024)
A laboratory experiment was carried out at Paklihawa Campus, Rupandehi starting from 15th December 2020 to 15th February 2021, to observe the efficacy of Eupatorium adenophorum extract against Callosobruchus chinensis (pulse beetle). A completely randomized design with two factors (altitude and concentration) was taken. Phytochemical screening and allelopathic test were completed during the research. Samples were collected from three altitudes, viz., Paklihawa, Hemja, and Tansen, and at three levels of concentration (5%, 10%, and 15%). This study explored the potential of E. adenophorum leaf extract as a natural pesticide against pulse beetles in stored pigeon peas. Phytochemical screening confirmed bioactive compounds like alkaloids, flavonoids, and terpenoids. Extracts from different altitudes and concentrations (5%, 10%, and 15%) were tested, revealing that higher altitude samples and higher concentrations significantly increased beetle mortality, achieving complete mortality by the tenth day at 15%. The extract also showed inhibitory effects on pigeon pea germination, suggesting allelopathic properties. Overall, E. adenophorum offers an eco-friendly alternative for pulse beetle management, supporting sustainable pest control practices.